Planerade hemförlossningar i Norden : kvinnors och barnmorskors perspektiv - Sjöblom, Ingela (Malmö högskola, Institutionen för vårdvetenskap (VV), 2014)
Background: Home birth is common in an international perspective but in the West it is a rare occurrence. In the Nordic countries, Iceland and Denmark have the highest home birth rates with about two per cent, Norway and Sweden approximately one per thousand, and in Finland only a dozen women a year give birth to their children in the home. Background: Home birth is common in an international perspective but in the West it is a rare occurrence. In the Nordic countries, Iceland and Denmark have the highest home birth rates with about two per cent, Norway and Sweden approximately one per thousand, and in Finland only a dozen women a year give birth to their children in the home. Data collections and methods: Two interview studies (study I and V) and three questionnaire studies (study II, III and IV) were carried out. The interviews were analyzed with phenomenological-hermeneutical respectively phenomenological approach and the questionnaires with content analysis and descriptive statistical analysis, in study III as parts of the mixed method. Results: Women giving birth at home experience that they can give birth in their own terms with selected supporters around them in an environment where they feel safe (study I). They state that they are highly satisfied with their home birth midwives (study IV). The midwives described their work with assisting home birth as a lifestyle, with an opportunity to realize their full midwifery competence (study V). Women feel that they in a negative way are treated as irresponsible as they choose to give birth at home, and that this seems to strengthen their position to realize it (study II and III). Conclusion: The few women who choose to give home birth in Sweden are highly satisfied with their births experience. They have experienced that people around them, healthcare professionals as well as private individuals, were adverse to their choice and tried to make them change their minds. Women in the Nordic countries experienced that the midwife who assisted the home birth ...